2015
DOI: 10.1167/iovs.14-15739
|View full text |Cite
|
Sign up to set email alerts
|

Latest Updates on Antiretinal Autoantibodies Associated With Vision Loss and Breast Cancer

Abstract: Cancer-associated retinopathy (CAR) is an uncommon paraneoplastic disorder of the retina that is frequently associated with breast cancer in pre- and postmenopausal women older than 50 years. In this review, we will give an update on the current knowledge regarding the association of antiretinal autoantibodies with the breast-CAR syndrome. Women with breast cancer and visual indications of CAR have a significantly increased incidence of autoantibodies (AAbs) against retinal proteins when compared to healthy wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 90 publications
(134 reference statements)
1
32
0
Order By: Relevance
“…The average age was 56.4 (50–62) years. Adamus et al reported that the onset of CAR in breast cancer was more common among women ≥ 50 of age, around the time of menopause, which is consistent with this study [ 6 ].…”
Section: Case Presentationsupporting
confidence: 92%
See 1 more Smart Citation
“…The average age was 56.4 (50–62) years. Adamus et al reported that the onset of CAR in breast cancer was more common among women ≥ 50 of age, around the time of menopause, which is consistent with this study [ 6 ].…”
Section: Case Presentationsupporting
confidence: 92%
“…Among the case reports including other tumors to date, CAR has led to the discovery of primary tumors in many cases. However, Adamus et al reported that the anti-retinal cell line antibodies in many breast cancer patients are already expressed before the onset of breast cancer, causing vision disorders 2 or 3 years after the cancer diagnosis, whereas CAR precedes the diagnosis of cancer in only 5% of cases [ 6 ]. One case involved breast cancer with distant metastasis.…”
Section: Case Presentationmentioning
confidence: 99%
“…The 23-kDa protein did not correspond to anti-recoverin antibody. Although recoverin has been historically shown to be a target antigen in CAR the incidence of anti-recoverin antibodies in CAR is very low across different kinds of tumor and ranges between 3% and 5% [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating anti-ENO1 antibodies have been found in several autoimmune disease such as lupus nephritis (66,67) and autoimmune retinopathy (68) as well as in cancer-associated retinopathy (69,70). In breast cancer patients with associated retinopathy an increased incidence of autoantibodies in general has been observed (71,72). Moreover, antibodies against citrullinated ENO1 epitopes were observed in rheumatoid arthritis patients (73,74).…”
Section: Immune Response To Tumor Associated Antigens In Cancer Patientsmentioning
confidence: 99%